1960
DOI: 10.1111/j.1423-0410.1960.tb04669.x
|View full text |Cite
|
Sign up to set email alerts
|

The Antigenic Nature of Heat‐Treated Human Plasma Protein Fractions

Abstract: Summary The Ouchterlony and Grabar technics have been applied to a study of three fractionated, heated plasma protein solutions. Two of these products, namely, Chalb albumin and SPPS, have been shown previously to produce reactions or antibodies in humans. It was confirmed that Chalb albumin possesses at least one antigen not present in normal unheated human serum. SPPS was shown to be atypical when compared to human serum protein. The possibility that protein complexes or modified proteins in Chalb albumin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1970
1970
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In conclusion, it should be noted that some studies [11,13] Of the different albumins, only OxgPA had an electrophoretic mobility differing from that of native albumin and this was attributed to the coupling of negatively charged hapten groups.…”
Section: (3)mentioning
confidence: 99%
“…In conclusion, it should be noted that some studies [11,13] Of the different albumins, only OxgPA had an electrophoretic mobility differing from that of native albumin and this was attributed to the coupling of negatively charged hapten groups.…”
Section: (3)mentioning
confidence: 99%
“…Some preparations exposed to the same heating procedure did not exhibit the new antigen, indicating that heating alone did not produce the new antigen. Lundblad et al [1] showed that human plasma protein fractions (88% albumin, 8% a-globulin and 4% /?-globulin) heated for 10 h at 60 °C were free of any antigen foreign to human serum and were nonreactive and nonantigenic when used clinically. Wolberg et al [4] determined that aggregates of mildly denatured albu min had antigenic determinants which were not found in native or dena tured unaggregated bovine albumin.…”
Section: Maurer and Subrahmanyammentioning
confidence: 99%
“…We considered it important to test for the presence of foreign antigens in the pro duct as these have previously been reported in products of heat fractionation [14].…”
Section: Safetymentioning
confidence: 99%